Diseño para una estructura de la gestión empresarial basada en el análisis de planificación estratégica, y comunicación organizacional aplicada para el Banco Nacional de Fomento Sucursal Chunchi. - Pomaquiza Lema, María Norma (2014)
The issue raised thesis aimed to determine the level of implementation of the strategic plan and organizational communication applied to the National Development Bank, Branch Chunchi. The contribution of this analysis was to visualize the organization from another context through basic business management tools and transcend a change of advanced models, strategies and mechanisms for smooth business operations facilitating their presence in an Increasingly competitive environment. Studied organizational communication more efficient ways within the organization thereby achieving the desired objectives and project a good corporate image. The results show that communication and strategic planning is essential, it helped to strengthen the image of organizational leadership and determined how to improve service to its external pubic, it was a form of management knowledge and correction actions could transgress production systems directly involved in the interaction of organizational structure.